ALICE: A new inflation monitoring tool - Gabe J. de Bondt; Elke Hahn; Zivile Zekaite (European Central Bank (ECB), 2018)
This paper develops Area-wide Leading Inflation CyclE (ALICE) indicators for euro area headline and core inflation with an aim to provide early signals about turning points in the respective inflation cycle. The series included in the two composite leading indicators are carefully selected from around 160 candidate leading series using a general-to-specific selection process. The headline ALICE includes nine leading series and has a lead time of 3 months while the core ALICE consists of seven series and leads the reference cycle by 4 months. The lead times of the indicators increase to 5 and 9 months, respectively, based on a subset of the selected leading series with longer leading properties. Both indicators identify main turning points in the inflation cycle ex post and perform well in a simulated real-time exercise over the period from 2010 to the beginning of 2018. They also have performed well in forecasting the direction of inflation. In terms of the quantitative forecast accurracy, the headline ALICE has on average performed broadly similarly to the Euro Zone Barometer survey, slightly worse than the Eurosystem/ECB Staff macroeconomic projections and better than the Random Walk model, albeit this is not the case for the core ALICE.
Keywords: C32; C52; C53; E31; E37; 330; euro area inflation; trend-cycle decomposition; band pass filter; leading indicators; forecasting